Social enmity, the state of exception, and the early modern roots of biopolitics: Michel Foucault and Giorgio Agamben read Thomas Hobbes - Paszyński, Piotr (2024)
This thesis develops a detailed examination of the claims made by two key contemporary political philosophers — Michel Foucault and Giorgio Agamben — concerning the relationship between sovereignty and biopolitics. I argue that both Foucault and Agamben use the concept of sovereignty in two distinct, yet interrelated meanings. First of all, they understand sovereignty to be a tool, or a strategy of domination, linked but not limited to the exercise of State power. For both, I argue, sovereignty understood as a strategy of domination operates simultaneously at the ‘macro‘ and ‘micro’ levels. That is to say, what they call sovereign power is exercised simultaneously at the level of the State, as well as at the level of everyday practices and apparatuses of power. It is both as the micro and the macro strategy of power that for Foucault and Agamben sovereignty is constituted as a strategy of domination. However, both Foucault and Agamben employ the concept of sovereignty with a second, different meaning. They understand sovereignty not only as a strategy of domination, but also as a certain language, concept, and practice taken up and developed in the long traditions of revolutionary thought and practices. As such, sovereignty is an ambiguous concept picked up both by the political right, by reactionary and fascist thinkers like Carl Schmitt, as well as on the political left to think and practice forms of revolutionary sovereignty. My argument is that what Foucault and Agamben aim to assess through their respective critiques of sovereignty is the extent to which emancipatory political tradition should have recourse to the concept of sovereignty even in its radical variation. In this thesis, I interrogate aspects of that critique by looking at their interpretations of Thomas Hobbes, a classic conservative-reactionary thinker of State sovereignty whose thought produced one of the most famous political images — the Leviathan — located at the frontispiece of the book under the same title. I treat Foucault’s and Agamben’s interpretations of Hobbes, his theory of sovereignty, and the political image of the Leviathan as examples of how this critique of sovereignty is employed, elaborated, and developed in their theoretical practice.